Role of hydroxychloroquine in preconception period of recurrent miscarriage patients - Mamta Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Three or more times of embryonic or fetal losses is termed as recurrent pregnancy loss (RPL). 1-2% women globally suffer from RPL which in turn causes physical and emotional devastation in such women. A deregulation of immune cells and cytokines is observed in women with RPL. Immunomodulatory drugs like hydroxychloroquine (HCQ) could thus be a justifiable line of therapy for normal conceiving in women who encountered RPL. Thus, the objective of current study was to evaluate whether oral administration of HCQ 200 mg twice a day in preconception period would improve conception and pregnancy outcome in RPL patients or not. Methods: Total 50 women with history of RPL and difficulty in conception were given 200 mg bd of HCQ orally twice a day along with once a day 5 mg dose of folic acid. To the above treatment protocol low dose ecosprin was added immediately after positive pregnancy test. After 20 weeks, HCQ dose was terminated while ecosprin was continued. Iron, calcium and protein supplements were continued in all patients. Results: 36 patients out of 50 who received HCQ conceived easily. Majority of patients who received the treatment protocol remained asymptomatic and exhibited no severe adverse effects. Out of 36 patients who conceived total 15 patients had normal delivery while 8 patients underwent lower segment caesarean section (LSCS) at term end and 5 patients had to undergo preterm delivery. Conclusions: HCQS use in preconception period facilitate conception and prevent miscarriage in refractory cases of RPL.